Review of marine animals and bioinspired robotic vehicles: Classifications and characteristics. (August 2017) - Zimmerman, S.; Abdelkefi, A.
Abstract: Marine robots are a developing topic for military, scientific, and environmental missions. However, most existing marine robots are either limited to flight or limited to swimming. Therefore, the combination of both provides endless possibilities for tasks, such as espionage, pollution and marine wildlife surveillance, and border protection. Applying bioinspiration and biomimetics not only camouflages the robot, but also increases the efficiency of already perfected designs. Because bioinspiration and aerial-aquatic locomotion are the main attraction for this article, this review gathers the characteristics of aerial-aquatic animals useful for such designs. These animals are diving birds and flying fish, specifically plunge-diving birds, surface-diving birds, both plunge- and surface-diving birds, two-winger flying fish, and four-winger flying fish. The overview of the current marine bioinspired and non-bioinspired robots that are both aerial and aquatic are also presented, followed by the limitations and recommendations of the bioinspired robots. It is shown by a comparison between the bioinspired robot and its corresponding animal that the existing robotic systems are not truly bioinspired. The main traits these systems are missing are replicating the exact weight, size, muscle movement, and skin texture of the biological animal. In order to have efficient robots, bioinspiration needs to be perfected. Doing so requires not only the basic design to be replicated, but every detail of the system to be imitated.